2022
DOI: 10.3389/fonc.2021.773345
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transperitoneal and Retroperitoneal Robotic Partial Nephrectomy for Patients With Complete Upper Pole Renal Tumors

Abstract: ObjectivesWe compared the outcomes of transperitoneal robotic partial nephrectomy (TRPN) and retroperitoneal robotic partial nephrectomy (RRPN) for complete upper pole renal masses (1 point for the “L” component of the RENAL scoring system).Material and MethodsWe retrospectively reviewed patients who underwent either TRPN or RRPN from 2013 to 2016. Baseline demographics and perioperative, functional, and oncological results were compared. Multivariable analysis was performed to identify factors related to pent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
(38 reference statements)
3
8
0
Order By: Relevance
“…Combined with the data mentioned above, the patient’s tumor size, RENAL score, preoperative renal function and ischemia time had no significant difference, so it is logical and credible that there was an absence of difference in postoperative functional and oncological outcomes. In addition, our research reported renal function and tumor termination similarly to the previous literature [ 13 , 16 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Combined with the data mentioned above, the patient’s tumor size, RENAL score, preoperative renal function and ischemia time had no significant difference, so it is logical and credible that there was an absence of difference in postoperative functional and oncological outcomes. In addition, our research reported renal function and tumor termination similarly to the previous literature [ 13 , 16 ].…”
Section: Discussionsupporting
confidence: 86%
“…Despite these limitations, our comparative study remains the initial report of TRPN and RRPN in completely lower pole renal masses. The current study should be seen as a complement to our previous studies on completely endophytic and completely upper polar renal tumors [ 13 , 16 ]. All three studies together confirmed that RRPN and TRPN have similar and reliable benefits for renal tumors in different locations.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Takagi et al compared TP and RP approaches when treating lateral tumors while Gu and colleagues investigated the same in the upper pole with findings in both studies showing lower estimated blood loss (EBL) and a shorter length of stay (LOS) in RP approach patients and similar complication rates between RP and TP approaches. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%